Theoretical investigations on the U2Mo3Si4 compound from first-principles calculations. (January 2020) - Song, Jiexi; Guo, Yaolin; Bu, Moran; Liu, Zhen; Shi, Diwei; Huang, Qing; Du, Shiyu
Abstract: With U3 Si2 being regarded as a prominent candidate fuel for LWR accident tolerant fuel, the importance on the ternary system such as the U–Mo–Si compounds also arises. However, the properties of the U–Mo–Si ternary system have barely been mentioned by theoretical study up to now. Here a systematic first-principles study for U2 Mo3 Si4 has been investigated on its structural, electronic, elastic, thermodynamic properties and defect energetics via the density functional theory. The conclusion shows that the U2 Mo3 Si4 compound is metallic and ductile. The calculated phonon dispersion curve indicates that U2 Mo3 Si4 is dynamically stable. In addition, the internal energy ( E ), Helmholtz free energy ( F ), entropy ( S ) and heat capacity ( C V ) are also calculated. The formation energies of different vacancies are obtained. The theoretical investigation in this paper may help with coming up with new thoughts for the design of ternary uranium fuels. Highlights: A comprehensive theoretical study of U2 Mo3 Si4 has been investigated using the first-principles approach. The U2 Mo3 Si4 compound is found to be mechanically stable and ductile. The Si vacancy is more readily produced.